2011
DOI: 10.1159/000333259
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Therapy after Curative Treatment for Hepatocellular Carcinoma

Abstract: It is widely accepted that hepatocellular carcinoma (HCC) has an annual recurrence rate of approximately 15–20% even after potentially curative treatment, with the 5-year recurrence rate reaching 80–90%. This recurrence rate is also known to be similar after various curative treatments including resection, percutaneous ethanol injection therapy, and radiofrequency ablation. Generally, in treating patients with HCC associated with hepatitis C or liver cirrhosis, aggressive efforts to prevent secondary carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 67 publications
1
34
0
Order By: Relevance
“…Effective strategies for the prevention of HCC recurrence are needed to improve the prognosis of patients with HCC (37). In this study, we demonstrated that the inflammatory cytokine IL6 stimulates the autocrine IGF loop to activate IGFIR, and initiates OCT4 (and/or NANOG) expression in HBV-HCC cells (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Effective strategies for the prevention of HCC recurrence are needed to improve the prognosis of patients with HCC (37). In this study, we demonstrated that the inflammatory cytokine IL6 stimulates the autocrine IGF loop to activate IGFIR, and initiates OCT4 (and/or NANOG) expression in HBV-HCC cells (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…However, the high annual recurrence rate (approximately 20%) is still a huge hurdle before achieving long-term disease-free survival [74] . Neoadjuvant and adjuvant therapy for resectable HCC is still a difficult challenge.…”
Section: Hepatatocarcinogenesis and Oxidative Stressmentioning
confidence: 99%
“…Activation of the Ras/mitogen-activated protein kinase pathway is a common finding in neoplastic processes (including in HCC) and is a determinant for promoting cell proliferation and the survival of tumor cells. This makes sorafenib an interesting drug; its use as a treatment for unresectable HCCs and as an adjuvant treatment before and after HCC recurrence is being investigated [50] . A study from Spain demonstrated that combination therapy resulted in an overall response (in accordance with the Response Evaluation Criteria in Solid Tumors) rate of 3.8% (1/26), and there was sustained stabilization of disease in 13 additional cases (50.0%) [42] .…”
Section: Treatment For Multiple Recurrencementioning
confidence: 99%